2020
DOI: 10.30714/j-ebr.2020258647
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of serum concentrations of leptin, homocysteine and insulin resistance in children with steroid-sensitive nephrotic syndrome

Abstract: To measure serum leptin, homocysteine concentrations and insulin resistance in active and remission stages of children with nephrotic syndrome (NS) and to investigate their role in NS pathogenesis. Methods: A total of 70 children were included in the study, 40 patients who had been diagnosed with NS and 30 healthy patients were control. Changes in plasma concentration of the serum homocysteine, leptin, and insulin were measured and compared with the other parameters in the groups. Results: Serum leptin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, studies have reported conflicting results regarding the level of serum leptin in the acute phase of NS compared with the remission phase levels. Some studies found lower (25,26,67), and others found unchanged (23,68) or higher (69) levels of leptin in the acute phase of NS compared with the remission phase. Our results are consistent with those studies that found lower levels of leptin during the acute phase of NS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have reported conflicting results regarding the level of serum leptin in the acute phase of NS compared with the remission phase levels. Some studies found lower (25,26,67), and others found unchanged (23,68) or higher (69) levels of leptin in the acute phase of NS compared with the remission phase. Our results are consistent with those studies that found lower levels of leptin during the acute phase of NS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a high level of leptin concentration is associated with CKD progression and its complications (22). To date, studies regarding leptin in pediatric patients with NS have reported inconsistent results, and its role in this condition remains unclear (23)(24)(25)(26). Programmed cell death ligand 1 (PD-L1) is a transmembrane protein expressed on immune, epithelial, endothelial cells and various other cell types, and its interaction with PD-1 plays a crucial role in maintaining immune tolerance and regulating immune responses (27).…”
Section: Introductionmentioning
confidence: 99%